A combined use of microscopic traffic simulation and extreme value methods for traffic safety evaluation. (May 2018) - Wang, Chen; Xu, Chengcheng; Xia, Jingxin; Qian, Zhendong; Lu, Linjun
Highlights: A combined usage of microscopic traffic simulation and Extreme Value Theory (EVT) was proposed for safety evaluation. Three calibration strategies were applied: a base strategy, a semi-calibration strategy, and a full-calibration strategy. EVT-based methods were employed to model both simulated/field conflict data and derive the Estimated Annual Crash Frequency (EACF). EVT based on the full-calibration strategy appears to be a better choice for simulation-based safety evaluation. Abstract: This paper proposes a combined usage of microscopic traffic simulation and Extreme Value Theory (EVT) for safety evaluation. Ten urban intersections in Fengxian District in Shanghai were selected in the study and three calibration strategies were applied to develop simulation models for each intersection: a base strategy with fundamental data input, a semi-calibration strategy adjusting driver behavior parameters based on Measures of Effectiveness (MOE), and a full-calibration strategy altering driver behavior parameters by both MOE and Measures of Safety (MOS). SSAM was used to extract simulated conflict data from vehicle trajectory files from VISSIM and video-based data collection was introduced to assist trained observers to collect field conflict data. EVT-based methods were then employed to model both simulated/field conflict data and derive the Estimated Annual Crash Frequency (EACF), used as Surrogate Safety Measures (SSM). PET was used for EVT measurement for three conflict types: crossing, rear-end, and lane change. EACFs based on three simulation calibration strategies were compared with field-based EACF, conventional SSM based on Traffic Conflict Techniques (TCT), and actual crash frequency, in terms of direct correlation, rank correlation, and prediction accuracy. The results showed that, MOS should be considered during simulation model calibration and EACF based on the full-calibration strategy appeared to be a better choice for simulation-based safety evaluation, compared to other candidate safety measures. In general, the combined usage of microscopic traffic simulation and EVT is a promising tool for safety evaluation.